2013
DOI: 10.1590/abd1806-4841.20132052
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis: correlation between severity index (PASI) and systemic treatment

Abstract: BACKGROUND Psoriasis is a chronic inflammatory disease of the skin that affects patients of all ages andboth genders. The impact of the disease on quality of life is greater among patients with moderate to severe psoriasis. OBJECTIVE to establish a correlation between the psoriasis area and severity index (PASI) and theDermatology Life Quality Index (DLQI) based on a quality of life questionnaire adapted to the Brazilian contextfor patients with plaque psoriasis before and after systemic treatment. METHODSThis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 16 publications
(11 reference statements)
4
18
0
1
Order By: Relevance
“…Psoriasis is a relatively common, chronic condition affecting between 1% and 3% of the general population (Grob and Folchetti, 1999;Koo, 1996;da Silva et al, 2013). Classic psoriasis vulgaris usually appears in specific areas including the elbows, knees and scalp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoriasis is a relatively common, chronic condition affecting between 1% and 3% of the general population (Grob and Folchetti, 1999;Koo, 1996;da Silva et al, 2013). Classic psoriasis vulgaris usually appears in specific areas including the elbows, knees and scalp.…”
Section: Introductionmentioning
confidence: 99%
“…DLQI has-been found highly sensitive to improvements in psoriasis symptoms and shows a positive correlation with the psoriasis area severity index (PASI) (Basra et al, 2008;Revicki et al, 2008). There are relatively few studies in the literature examining the correlation between quality of life and symptom severity in patients with psoriasis (da Silva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Methotrexate inhibits the dihydrofolate reductase enzyme, which plays a key role in the folate cycle. 6 Only four studies have stated that polymorphisms of the MTHFR gene could be associated with methotrexate efficacy in psoriasis patients. 21,24 Chandran et al and Campalani et al demonstrated that MTHFR 677TT polymorphism may be related to methotrexate-induced liver toxicity in Canadian and UK populations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Furthermore, some studies reported increased levels of plasma homocysteine and a decreased folic acid concentration in psoriasis patients. 4,6 Today, hyperhomocysteinemia is a recognised risk factor for cardiovascular diseases and psoriasis. 4,7 …”
Section: Introductionmentioning
confidence: 99%
“…Essas doenças podem estar presentes desde a infância e afetam a qualidade de vida do paciente ao interferir negativamente nos âmbitos físico, social e emocional de sua vida (Alvarenga & Caldeira, 2009;Barbarot et al, 2007;Gon, Gon, & Zazula, 2013;Manzoni et al, 2012;Silva, Fortes, Miot, & Marques, 2013;Tejada, Mendoza-Sassi, Almeida, Figueiredo, & Tejada, 2011;Torres, Silva, Magalhães, Morcillo, & Velho, 2011;Weber, Lorenzini, Reinehr, & Lovato, 2012). Rotina de tratamento, cuidados constantes com a pele, restrição na participação em atividades esportivas e de lazer e exposição a situações de estigmatização pela visibilidade das lesões podem dificultar a adaptação à doença e tornar-se um evento estressor recorrente (Castro & Piccinini, 2002;Gon, Rocha, & Gon, 2005;Pires & Cestari, 2005).…”
Section: Introductionunclassified